The continuity of ‘continuity’: flow and the changing experience of watching broadcast television - Johnson, Catherine (Spokesman Books, 2013)
It has been widely argued that the experience of watching television has altered significantly since Raymond Williams’s theorisation of flow in the mid-1970s. Yet despite the rise of new technologies such as personal video recorders and on-demand services, broadcast television remains the primary way in which television is viewed in the West. This article, therefore, asks whether Williams’s theorisation of flow has continued significance in understanding the nature of broadcast television in the digital era. Focusing on the broadcast junctions, identified by Williams as a fundamental part of the broadcast flow, it examines the changing ways in which broadcasters have constructed and explained the value and experience of television from the 1980s to the 2000s. In doing so, it argues that we need to be as attuned to the continuities and similarities as the differences if we are to understand the changes to television wrought by digital.